The Role of Religiosity and Spirituality as Efforts to Prevent Financial Reporting Fraud - Istiariani, Irma (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The research about fraudlent financial reporting prevention has been often done to be researched, but when it was linked with religiousity and spirituality it has been rarely done. This study aims to explain how the role of religiousity, and spirituality in prevent fraudulent financial reporting. This study used qualitative research methodology with descriptive analysis. The results of this study state that it is necessary to strengthen the role of religiosity and spirituality so that fraudulent financial reporting not happen again in many corporation in Indonesia. This study recommended that there are needed strengthen of religiousity and spirituality to prevent fraudulent financial reporting practice many company in Indonesia.